Structural stigma and sexual minority men's depression and suicidality: A multi-level examination of mechanisms and mobility across 48 countries: John Pachankis. (25th October 2022) - Pachankis, J; Hatzenbuehler, ML; Bränström, R; Schmidt, AJ; Berg, RC; Jonas, K; Pitoňák, M; Baros, S; Weatherburn, P
Abstract: Background: Sexual minority men are at greater risk of depression and suicidality than heterosexuals. Stigma, the most frequently hypothesized risk factor for this disparity, operates across socioecological levels-structural (e.g., laws), interpersonal (e.g., discrimination), and individual (e.g., self-stigma). However, there is limited data on whether changes in structural stigma, such as when a stigmatized person moves to a lower stigma context, affect mental health, and on the mechanisms underlying this association Methods: The current study uses data from the 2017/18 European Men-who-have-sex-with-men Internet Survey (n = 123, 428), which assessed mental health and psychosocial mediators. We linked these data to an objective indicator of structural stigma related to sexual orientation in respondents' countries of origin (N = 178) and receiving (N = 48) countries Results: Among respondents who moved from higher-to-lower structural stigma countries (n = 11, 831), longer exposure to the lower structural stigma environments of their receiving countries was associated with a significantly: 1) lower risk of depression and suicidality; 2) lower odds of concealment, internalized homonegativity, and social isolation; and 3) smaller indirect effect of structural stigma on mental health through these mediators. Conclusions: This study provides evidence that structural stigma is associated with the mental health of sexual minority men, both through proximal experiences and as a function of length of exposure to structurally diverse contexts, at least for those who move higher-to-lower structural stigma contexts. Findings suggest the importance of routinely assessing life-course structural influences on mental health and deploying interventions to address those influences.